TGF-beta s and cAMP regulate GAP-43 expression in Schwann cells and reveal the association of this protein with the trans-Golgi network - Stewart, H J; Curtis, R; Jessen, K R; Mirsky, R (The European journal of neuroscience, 1995)
We have shown previously that growth-associated protein 43 (GAP-43) is expressed by rat Schwann cells and is restricted to non-myelin-forming Schwann cells in vivo. Here we examined the regulation of GAP-43 using agents that are known to control Schwann cell differentiation in vitro. GAP-43 protein and mRNA levels are decreased by forskolin and other agents that elevate intracellular cAMP (and promote expression of the myelinating Schwann cell phenotype). We also found that expression of GAP-43 protein but not mRNA is down-regulated by transforming growth factor betas (TGF-beta s). Moreover, TGF-beta treatment of Schwann cells results in cell clumping, process retraction and disappearance of GAP-43 from the plasma membrane, revealing that GAP-43 is associated with the Golgi apparatus. This association was confirmed by partial overlap of GAP-43 with the trans-Golgi network marker (23c) and the disruption of the Golgi with brefeldin A or monensin leading to altered GAP-43 distribution. Golgi-associated GAP-43 appeared to have the same molecular weight as the plasma membrane-associated GAP-43. Thus these results show that GAP-43 expression in Schwann cells is subject to regulation by both extracellular and intracellular signalling molecules and that Schwann cell GAP-43 is often associated with the Golgi apparatus.